Eco-trap: An Innovative Low-Cost Trash Trap to Remove Solid Waste on River Surface - Soh, Wee Shong; Ali, Roslinda; Abdullah, Nor Maizzaty (Progress in Engineering Application and Technology, 2021)
The rapid development in Malaysia from agriculture, industrial and commercial sectors have resulted in many environmental problems including the solid waste and water pollutions. In year 2010, Malaysia had ranked as the 8th country with highest mismanaged plastic waste entered the oceans. On top of that, in 2012, 41% of the rivers in Malaysia were classified as polluted. Therefore, this research is interested to design a cost-effective and eco-friendly trash trap that can be used as an instrument to clean the river. The prototype, called eco-trap, is designed to trap the solid waste on the river surface. Eco-trap is made from plastic bottle waste and it was installed at the Panchor River to test for its trapping performance. The data collection was conducted for a month with four times of waste collection. At the end of the testing period, a total of 953.5kg of solid waste were collected using eco-trap. Bulky waste recorded the highest weight composition of 620.5 kg (51%). This is followed by plastic waste (217 kg, 35%), steel can waste (61 kg, 10%) and aluminium can waste (24.5 kg, 4%). All in all, it can be concluded that the prototype had successfully trapped the wastes flow into the study area and helped in river cleaning process.